Thinking with your hands : the surprising science behind how gestures shape our thoughts - Goldin-Meadow, Susan (Basic Books, Hachette Book Group, 2023)
"Imagine a friend who earnestly tells you that he thinks men and women are equally good leaders. But when he talks about men's leadership skills, he places his palm at eye-level, and when he talks about women's leadership skills, he places his palm a bit lower, at mouth-level. His hands have given him away: even if he truly thinks that his views are egalitarian, he holds an implicit belief that is now there for all the word to see. You swear you heard him say something disparaging, even if you don't fully realize why. In Thinking With Your Hands, cognitive psychologist Susan Goldin-Meadow reveals just how essential gestures are to how we think and communicate. Drawing on decades of research, including experiments and studies from throughout her own illustrious career, Goldin-Meadow presents the definitive overview of the most important feature of human communication that you've never thought about. Gesture is a universal behavior common to every culture and language. It's found among Deaf people who use their hands to speak in sign language and blind people who have never seen anyone gesture before. Far from being an affective flourish, Goldin-Meadow argues, gestures are an integral piece of the conversation-even if we don't realize it while we're using them. They give form to ideas that are difficult to phrase in language and help us express ideas that we are grappling with but haven't yet fully grasped. Indeed, understanding gesture compels us to re-think everything from to how we set development milestones for children, to what's admissible in a court of law, to whether FaceTime is a good communication technology. A landmark achievement by a star in the field of cognitive psychology, Thinking With Your Hands reveals the entire landscape of communication that's hidden in our hands and promises to transform the way we think about language for decades to come"--